2023
DOI: 10.1111/jns.12570
|View full text |Cite
|
Sign up to set email alerts
|

The autoimmune vulnerability of the node of Ranvier

Abstract: The nodes of Ranvier (NoR) are essential domains for nerve conduction and their disruption plays a key role in the pathophysiology of immune-mediated neuropathies. Our understanding of the specialized nodal regions and the immune mechanisms that affect them is growing and has led to the update of peripheral neuropathy classification to include the autoimmune nodopathies, defined by the site of the autoimmune attack. Autoantibodies directed against molecules of the nodal region (as neurofascin-140/186, neurofas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 157 publications
0
2
0
Order By: Relevance
“…It is well established that autoantibodies are a mechanism to cause peripheral neuropathy. For example, in inflammatory neuropathies such as GBS and Chronic Inflammatory Demyelinating Polyneuropathy (CIDP), antibodies targeting antigens within the PNS are known to drive pathology through mechanisms including macrophage or complement activation, as well as target disruption ( Querol et al, 2023 ). Furthermore, autoantibodies can directly impact sensory neuron physiology by disrupting ion channel function ( Dawes et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that autoantibodies are a mechanism to cause peripheral neuropathy. For example, in inflammatory neuropathies such as GBS and Chronic Inflammatory Demyelinating Polyneuropathy (CIDP), antibodies targeting antigens within the PNS are known to drive pathology through mechanisms including macrophage or complement activation, as well as target disruption ( Querol et al, 2023 ). Furthermore, autoantibodies can directly impact sensory neuron physiology by disrupting ion channel function ( Dawes et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of the immune system is thought to contribute with around 20% of SFN cases being associated with autoimmune conditions (e.g., Sjorgen’s syndrome, sarcoidosis) ( de Greef et al, 2018 ). Autoimmunity includes the action of autoantibodies and autoantibodies targeting antigens within the nervous system are known to have a role in other peripheral neuropathies and contribute to disease progression ( Querol et al, 2023 ). Furthermore, studies have shown that autoantibodies can directly drive neuropathic pain in patients by targeting antigens on sensory neurons ( Dawes et al, 2018 ), proposing similar mechanisms in SFN.…”
Section: Introductionmentioning
confidence: 99%